A Simulation Model to Study Maternal Hyperoxygenation During Labor. Issue 4 (December 2015) - Bullens, L.M.; Van Der Hout-Van Der Jagt, M.B.; Van Runnard Heimel, P.J.; Oei, G.
Abstract : ( Acta Obstet Gynecol Scand . 2014;93:1268–1275)